臺灣兩個自行發展的數學教學輔導模式 Two Self-Developed Mentoring Models for Mathematics Teaching in Taiwan - 鄭慧儒 Fui-Due Tee; 金鈐 Chien Chin (National Taiwan Normal University, 2012)
在臺灣，教師輔導制度已經從1994 年開始執行，但是，國內很多輔導教師似乎都沒有接受過訓練，所有的相關輔導模式都是自行發展的。由兩家學校所收集的資料，本文作者檢驗這兩家學校的數學教學輔導模式，並且將結果拿來和四個國際知名的模式相比較：學徒模式（apprenticeship）、能力本位模式（competence-based）、Anderson 和Shannon（1988）的模式、Furlong 和Maynard（1995）的模式，以及Jaworski和Watson（1994）的聯合輔導理念（ideas of co-mentoring）。本研究採用個案研究與紮根理論並行的質化研究方法。研究結果顯示：這兩家學校的模式與上述四個知名模式有共通之處，不過，集體輔導的部分則離聯合輔導關係（co-mentoring relationship）理念尚遠。 Since 1994, the teacher mentoring system in Taiwan has been compulsory; however, numerous teacher mentors remain untrained, and the related mentoring models are self-developed. Using data from two public senior high schools in Taiwan, this study investigates their mentoring models for mathematics teaching and compares them against four significant models, that is, apprenticeship mentoring model, competence-based mentoring model, Anderson and Shannon's (1988) mentoring model, and Furlong and Maynard's (1995) mentoring model, and with Jaworski and Watson's (1994) ideas of co-mentoring. This study employed a qualitative approach that combines a case study and grounded theory. The findings revealed that, without training, the two cases in this study include one-on-one mentoring and team mentoring. Both cases share a number of similarities with the four significant mentoring models; however, the team mentoring approach differs substantially from that of co-mentoring.